The finance-growth nexus in the age of financialisation: an empirical reassessment for the European Union countries - Barradas, R. (Dinâmia’CET-IUL Working Paper Nº 2018/07, 2018)
This paper draws an empirical reassessment of the finance-growth nexus by performing a panel data econometric analysis for all 28 European Union countries over 27 years from 1990 to 2016. Since the mid-1980s, the financial system has experienced a strong liberalisation and deregulation by preventing its beneficial effects on the real economy. This phenomenon, typically called financialisation, points to a negative view of finance and contradicts the well- entrenched hypothesis on the finance-growth nexus. We estimate both linear and non-linear growth models by incorporating seven proxies of finance (money supply, domestic credit, financial value added, short-term interest rate, long-term interest rate, stock market volume traded and stock market capitalisation) and five control variables (the lagged growth rate of the real per capita gross domestic product, the inflation rate, the general government consumption, the degree of trade openness and the education level of the population). Our results show that finance has impaired economic growth in the EU countries, both in the pre-crisis period and in the crisis and post-crisis periods. The enormous growth of domestic credit and of the financial value added have been restraining the economic growth of the EU countries since 1990 and particularly up until the Great Recession. This implies the need to reduce the prominence of finance, i.e. so-called de-financialisation, in the coming years in order to avoid the potential new ‘secular stagnation’ in the current age of financialisation.